Prognostic influence of witness/victim experiences and PTSD-specific symptoms on working and educational capacity: a comparison between two groups of individuals post-trauma - Mueller, Helge H.; Möller, Sebastian; Hilger, York; Sperling, Wolfgang (Annals of General Psychiatry, 2015)
Trauma exposure depends of the type of trauma and can result in the development of posttraumatic stress disorder (PTSD). The type of traumatization (such as Holocaust experiences and other sources of trauma) and specific symptoms of PTSD have influences on the outcome, and specific symptoms of PTSD influence personal and professional outcomes. Another factor is the role of the victim in their traumatization. Some patients are actively traumatized through being victims of torture, while others are passively traumatized by witnessing the traumatization of others.We compared two groups of victim/witness trauma sufferers (PTSD vs. Holocaust-experience PTSD (HE-PTSD)) with regard to PTSD symptoms, educational and working capacity, and functional outcome parameters.HE-PTSD survivors with victim/witness trauma experience showed substantially more specific PTSD symptoms and higher symptom-specific intensities but had high social function and education levels. The intensity and type of intrusive memories and sociodemographic factors do not seem to have a prognostic influence on working or educational outcomes.Identifying the combined victim/witness experience seems to play an important prognostic role in the assessment of PTSD victims. Further studies should consider these findings within other specific traumatization groups.
EVALuna2:22275